Stable Carbon Isotope Discrimination Is under Genetic Control in the C4 Species Maize with Several Genomic Regions Influencing Trait Expression . Issue 1 (26th November 2013) - Gresset, Sebastian; Westermeier, Peter; Rademacher, Svenja; Ouzunova, Milena; Presterl, Thomas; Westhoff, Peter; Schön, Chris-Carolin
Abstract : Multiplatform-based phenotyping and high-density genotyping uncovers multiple genomic regions controlling stable carbon isotope discrimination in a maize introgression library . Abstract: In plants with C4 photosynthesis, physiological mechanisms underlying variation in stable carbon isotope discrimination (Ɗ 13 C ) are largely unknown, and genetic components influencing Ɗ 13 C have not been described. We analyzed a maize ( Zea mays ) introgression library derived from two elite parents to investigate whether Ɗ 13 C is under genetic control in this C4 species. High-density genotyping with the Illumina MaizeSNP50 Bead Chip was used for a detailed structural characterization of 89 introgression lines. Phenotypic analyses were conducted in the field and in the greenhouse for kernel Ɗ 13 C as well as plant developmental and photosynthesis-related traits. Highly heritable significant genetic variation for Ɗ 13 C was detected under field and greenhouse conditions. For several introgression library lines, Ɗ 13 C values consistently differed from the recurrent parent within and across the two phenotyping platforms. Ɗ 13 C was significantly associated with 22 out of 164 analyzed genomic regions, indicating a complex genetic architecture of Ɗ 13 C . The five genomic regions with the largest effects were located on chromosomes 1, 2, 6, 7, and 9 and explained 55% of the phenotypic variation for Ɗ 13 C . Plant development stage had no effect on Ɗ 13 C expression, as phenotypic as well as genotypic correlations between Ɗ 13 C, flowering time, and plant height were not significant. To our knowledge, this is the first study demonstrating Ɗ 13 C to be under polygenic control in the C4 species maize.